2008
DOI: 10.2214/ajr.07.3485
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Cholecystectomy: Postoperative Imaging

Abstract: Laparoscopic cholecystectomy is a commonly performed surgical procedure and radiologists are often called on to identify or rule out postoperative complications. In such cases, the correct diagnosis is crucial in optimizing patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 67 publications
1
45
0
4
Order By: Relevance
“…9 However, and despite the widespread implementation of CVS, recent literature suggests that bile duct injury still occurs in 0.26% to 0.7% of procedures. 10-15 In addition, conversion to an open procedure is indicated in cases where CVS cannot be reached, with reported conversion-to-open rates in LC presently around 2.6% to 10%. 16-18 Conversion is often due to unclear (biliary) anatomy associated with a wider range of conditions including acute cholecystitis, acute biliary pancreatitis, bleeding in Calot’s triangle, fibrotic shrunken gallbladders due to previous infection, gallstones in Hartmann’s pouch, a short cystic duct, Mirizzi’s syndrome, or abnormal biliary anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…9 However, and despite the widespread implementation of CVS, recent literature suggests that bile duct injury still occurs in 0.26% to 0.7% of procedures. 10-15 In addition, conversion to an open procedure is indicated in cases where CVS cannot be reached, with reported conversion-to-open rates in LC presently around 2.6% to 10%. 16-18 Conversion is often due to unclear (biliary) anatomy associated with a wider range of conditions including acute cholecystitis, acute biliary pancreatitis, bleeding in Calot’s triangle, fibrotic shrunken gallbladders due to previous infection, gallstones in Hartmann’s pouch, a short cystic duct, Mirizzi’s syndrome, or abnormal biliary anatomy.…”
Section: Introductionmentioning
confidence: 99%
“…3,9 The reported occurrence rate of bile duct injury ranged from 0.4% to 4%. 10 It could prolong the hospital stay, and result in cholangitis and biliary cirrhosis. Hepatic failure could be the lethal complication after bile duct injury.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we hypothesized that particularly for cases of complicated cholecystolithiasis such as cholecystitis, biliary pancreatitis, surgery after endoscopic retrograde cholangiopancreatography, or percutaneous gallbladder drainage with The rate of bile duct injuries in single-incision laparoscopic surgery cholecystectomy is higher than in laparoscopic cholecystectomy: 0.7% versus 0.26%-0.6%, respectively. 8,39 This might be attributable to the different angle in which the surgical field is approximated or due to different positioning and introduction of a decreased number of trocars than in conventional laparoscopic cholecystectomy. Differences in visualization might impede or delay recognition of the extrahepatic bile ducts and increase the risk of iatrogenic bile duct injury.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, despite an initial decrease in bile duct injuries with the introduction of CVS, current literature suggests that bile duct injuries are still in the 0.26%-0.6% range. [3][4][5][6][7][8] Although this complication is rare, a patient with a common bile duct (CBD) injury is likely to have re-interventions, prolonged hospital admission, and a decreased quality of life and is faced with a 5%-9% mortality risk. [9][10][11][12][13] The 2011 consensus meeting of the European Association for Endoscopic Surgery in Turin, Italy, confirmed that prevention of bile duct injury remains a priority in the improvement of laparoscopic cholecystectomies.…”
Section: Introductionmentioning
confidence: 99%